Rancang Bangun Aplikasi Peminjaman Ruangan Pertemuan di Universitas Nasional Berbasis Web - Suryadi, Suryadi; Fitri, Iskandar; Nurhayati, Nurhayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The National University has a number of rooms that can be used by the entire academic community to support their activities. Currently, the use of the room is managed by the General Administration Unit (BAU) of the National University. Anyone who will use the room must apply for a permit to the BAU unit. The problem is, currently the existing process is still manual where the borrower must come directly to the unit. If the room has been borrowed by someone else or the BAU unit admin is not in place, then the borrower's efforts will be in vain. This is certainly not effective and efficient. This research designs and develops a Web-based application for borrowing meeting rooms at the National University. The application was designed using the Unified Modeling Language (UML) tool and developed with the PHP and MySQL languages. The result of this research is the availability of room loan applications at the National University. The results of testing the logic path with the white box testing method, testing is carried out on the admin and borrower flowcharts resulting in cyclomatic complicity 8, region 8, and independent path 8 logic paths that are good and have good functionality based on the black box method testing.
Keywords: Application for Borrowing Room; Web-Based Application; Waterfall Model; UML; White and Black Box Testing